Stress analysis by the finite element method in dental implants with morse cone platform. - Melo, Antônio Renato; Reiner, Fabio Alexandre (Brazilian Journal of Implantology and Health Sciences, 2020)
The prediction of the mechanical behavior of inclined dental implants is an important factor in the dental field and the Finite Element Method (FEM) is considered a tool for this purpose. Objective: to analyze the distribution of stresses and displacements in tapered Morse tapered implants with a diameter of 3.5 mm and abutments with 4.8 mm and 3.8 mm in diameter, submitted to compression loads (100 N and 200 N) , inclined at 20º and 45º with stainless steel base and cortical bone via MEF. Materials and method: two three-dimensional models of implants and abutments installed at an angle of 20º and 45º were used, which were subjected to compression loads in the vertical downward direction (Y-axis). Results: the maximum von Mises stresses showed higher values for geometries with a 45º inclination and 200 N. loading. It was also possible to verify that the results for implants subjected to 100 N at 45º loading presented higher values (574.16 MPa), when compared with literature data, with a difference of 8.7%. The same could be verified for displacement results, where the set of abutment-abutments with greater inclination (45º) presented higher values, when compared with abutment-abutments with less inclination (20º). Conclusion: it was possible to certify via MEF that the highest stresses are obtained for loads with greater slopes, and the same occurs for displacement values. MEF proved to be a viable alternative in the dental field to predict the mechanical behavior of dental implants.